Prevalence and Predictors of Gestational Diabetes Mellitus and Overt Diabetes in Pregnancy: A Secondary Analysis of Nationwide Data from India - Saurav Basu; Vansh Maheshwari; Rutul Gokalani; Chandrakant Lahariya (Preventive Medicine: Research & Reviews, 2024)
Background: This analysis was conducted to understand prevalence and determinants of gestational diabetes mellitus (GDM) and (overt) diabetes in pregnancy (DIP) in India, and also ascertain their health-seeking behaviour. Materials and Methods: The authors analysed data from the fifth National Family Health Survey of India. Binary logistic regression was used to assess the factors independently associated with GDM and (overt) DIP. Results: The weighted prevalence of GDM was 4.2% (95% confidence interval [CI]: 3.9–4.5), and the age-adjusted prevalence was 5.4% (95% CI: 4.5–6.4). The prevalence of GDM increased with age. The weighted prevalence of (overt) DIP was 0.38% (95% CI: 0.30–0.48), and the age-adjusted prevalence was 1.04% (95% CI: 0.64–1.68). On adjusted analysis, it was found that increasing age and obesity had significantly higher odds of having GDM. Higher odds of access to private facilities were found amongst women with higher education and those who were overweight. Significant regional variation in the prevalence of GDM was observed, with a very low burden observed in northeastern states and a comparatively higher burden in Central, Western and Southern Indian states. Conclusions: There is an increasing prevalence of GDM in India. Strengthening primary health systems to enhance GDM-related service availability, quality and delivery could be logical policy intervention.